Chloroplast Acetyltransferase NSI Is Required for State Transitions in Arabidopsis thaliana . Issue 8 (2nd July 2018) - Koskela, Minna M.; Brünje, Annika; Ivanauskaite, Aiste; Grabsztunowicz, Magda; Lassowskat, Ines; Neumann, Ulla; Dinh, Trinh V.; Sindlinger, Julia; Schwarzer, Dirk; Wirtz, Markus; Tyystjärvi, Esa; Finkemeier, Iris; et al.
Abstract : NSI is an active chloroplast Lys acetyltransferase required for state transitions in Arabidopsis independently of LHCII phosphorylation. Abstract: The amount of light energy received by the photosynthetic reaction centers photosystem II (PSII) and photosystem I (PSI) is balanced through state transitions. Reversible phosphorylation of a light-harvesting antenna trimer (L-LHCII) orchestrates the association between L-LHCII and the photosystems, thus adjusting the amount of excitation energy received by the reaction centers. In this study, we identified the enzyme NUCLEAR SHUTTLE INTERACTING (NSI; AT1G32070) as an active lysine acetyltransferase in the chloroplasts of Arabidopsis thaliana . Intriguingly, nsi knockout mutant plants were defective in state transitions, even though they had a similar LHCII phosphorylation pattern as the wild type. Accordingly, nsi plants were not able to accumulate the PSI-LHCII state transition complex, even though the LHCII docking site of PSI and the overall amounts of photosynthetic protein complexes remained unchanged. Instead, the nsi mutants showed a decreased Lys acetylation status of specific photosynthetic proteins including PSI, PSII, and LHCII subunits. Our work demonstrates that the chloroplast acetyltransferase NSI is needed for the dynamic reorganization of thylakoid protein complexes during photosynthetic state transitions.